2022
DOI: 10.3390/jcm11071807
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing MRONJ after Tooth Extraction in Cancer Patients Receiving Bone-Modifying Agents

Abstract: Background: Medication-related osteonecrosis of the jaws (MRONJ) is a mucosal lesion of the maxillofacial region with necrotic bone exposure. MRONJ is believed to be multifactorial. Tooth extraction is debatably a risk factor for MRONJ. The targets of the present study were to examine MRONJ occurrence in patients using bone modifying agents (BMAs) for oncology indications and undergoing a dental extraction, and to assess whether suspected predisposing factors can predict MRONJ. Materials and Methods: This retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Five of the included studies in this review reported that teeth with signs of inflammation, such as severe periodontal disease, osteomyelitis, or other symptoms of infection, before the treatment showed an increased risk of MRONJ after extraction (Hasegawa et al, 2019;Manfredi et al, 2017;Saia et al, 2010;Soutome et al, 2018;Yamazaki et al, 2012). The results therefore suggest that nonrestorable teeth and those with poor Also, two recently published studies performed in Japan (Hasegawa et al, 2021) and Israel (Avishai et al, 2022) confirm that local inflammation processes present even before tooth extraction increase the risk of MRONJ. These findings can support the hypothesis that a periodontal infection in combination with antiresorptive treatment initiates osteonecrosis and not tooth extraction itself.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Five of the included studies in this review reported that teeth with signs of inflammation, such as severe periodontal disease, osteomyelitis, or other symptoms of infection, before the treatment showed an increased risk of MRONJ after extraction (Hasegawa et al, 2019;Manfredi et al, 2017;Saia et al, 2010;Soutome et al, 2018;Yamazaki et al, 2012). The results therefore suggest that nonrestorable teeth and those with poor Also, two recently published studies performed in Japan (Hasegawa et al, 2021) and Israel (Avishai et al, 2022) confirm that local inflammation processes present even before tooth extraction increase the risk of MRONJ. These findings can support the hypothesis that a periodontal infection in combination with antiresorptive treatment initiates osteonecrosis and not tooth extraction itself.…”
Section: Discussionmentioning
confidence: 76%
“…However, in a Swedish prospective study with a 4‐year follow‐up, Hallmer et al (2018) indicated that pre‐existing inflammatory dental disease such as periodontal disease or periapical pathology is a well‐recognized risk factor, assessed as the initiating factor for the development of MRONJ in 18% and 4% of the cases, respectively. Also, two recently published studies performed in Japan (Hasegawa et al, 2021) and Israel (Avishai et al, 2022) confirm that local inflammation processes present even before tooth extraction increase the risk of MRONJ. These findings can support the hypothesis that a periodontal infection in combination with antiresorptive treatment initiates osteonecrosis and not tooth extraction itself.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations